2021
DOI: 10.1038/s41467-021-27414-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for redox control by the human cystine/glutamate antiporter system xc−

Abstract: Cysteine plays an essential role in cellular redox homoeostasis as a key constituent of the tripeptide glutathione (GSH). A rate limiting step in cellular GSH synthesis is the availability of cysteine. However, circulating cysteine exists in the blood as the oxidised di-peptide cystine, requiring specialised transport systems for its import into the cell. System xc− is a dedicated cystine transporter, importing cystine in exchange for intracellular glutamate. To counteract elevated levels of reactive oxygen sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 83 publications
5
66
0
Order By: Relevance
“…The less strict requirement of the tested residues suggests that b 0,+ AT uses multiple residues to recognize cystine. Notably, among SLC7 members, cystine transport is mediated by b 0,+ AT, xCT (SLC7A11) 46 , and AGT1 (SLC7A13) 8 , which show little conservation in the unwound region of TM6 (Supplementary Fig. 15 ) 41 , 45 .…”
Section: Resultsmentioning
confidence: 99%
“…The less strict requirement of the tested residues suggests that b 0,+ AT uses multiple residues to recognize cystine. Notably, among SLC7 members, cystine transport is mediated by b 0,+ AT, xCT (SLC7A11) 46 , and AGT1 (SLC7A13) 8 , which show little conservation in the unwound region of TM6 (Supplementary Fig. 15 ) 41 , 45 .…”
Section: Resultsmentioning
confidence: 99%
“…The recent studies reported the structures of the human xCT–4F2hc complex harboring consensus mutations in xCT at 6.2 Å resolution, 14 and in apo state at 3.4 Å resolution or in complex with glutamate at 3.7 Å resolution, respectively, which provide a structural basis for understanding xCT substrate (glutamate and cystine) recognition. 15 In contrast, we solved the cryo-EM structure of the erastin-bound human xCT–4F2hc complex at 3.4 Å resolution, revealing the site at which erastin binds and mediates the induction of ferroptosis. In this complex, the chlorophenoxy group in the erastin molecule functionally interacts with the Phe254 residue in the TM6b domain of xCT, thereby mediating erastin’s inhibitory effects of erastin and regulating erastin-induced ferroptosis; consistent with the finding that the chlorophenoxy moiety is required for inducting ferroptosis.…”
mentioning
confidence: 94%
“…Under physiological conditions, intracellular cystine is reduced to cysteine, which is involved in the synthesis of intracellular GSH. So, inhibition of SLC7A11 will cause decreasing of intracellular GSH level [ 17 ]. As an antioxidant defense enzyme, GPX4 can reduce toxic phospholipid peroxides (PL-OOH) to nontoxic lipid alcohols via using GSH as the substrate or electron donor [ 18 ].…”
Section: Discussionmentioning
confidence: 99%